Diplolaimella dievengatensis (Nematoda: Monhysteridae) as model organism in ecotoxicity assay - Oliveira, Nilvea Ramalho de (2017)
Free-living marine nematodes are the most ubiquitous, abundant and diverse meiofaunal component of benthic communities. These are excellent model organisms, due to its short life span, wide availability and feasibility to cultivate with minimum laboratory facilities. In this study, a population of Diplolaimella dievengatensis Jacobs 1991 (Nematoda, Monhysteridae) from the relatively Pristine estuary of the Guaratuba River in São Paulo, Brazil was isolated and cultivated. The goals were; i- to apply an integrative taxonomic approach in order to compare this population from Brazil with another from the species type-locality in the Belgian Coast, with regard to morphological, life-cycle and the 18S gene of the rDNA molecular data; and ii- to compare, at the light of life history theory, the responses of life history parameters such as; fecundity, growth and survivorship of D. dievengatensis (here as a slower species) and Litoditis marina (Bastian, 1865) (Nematoda, Rhabditidae) (as a faster species) under sublethal exposition to the sodium dodecyl sulfate (SDS) surfactant. The population from Brazil was similar to that from Belgium coast in all parameters. Although morphometric analyses considered the Brazilian D. dievengatensis isometrically larger than the Belgian population regarding some characters, the presence of all diagnostic characters confirmed the similarity of both species. The life-cycle, hatching time, final body length, and biomass parameters were similar in both populations, in which females were larger than males. The population growth, measured as intrinsic rate of natural increase was slightly higher for the D. dievengatensis from Brazil (rm=0.41), than the European population (rm =0.348). Molecular comparison on Genbank showed 99.4% of similarity between both populations, indicating therefore, that D. dievengatensis from Brazil is similar to those from Belgium. In the chapter ii, both species responded differently to SDS exposition. Growth and reproduction rate of D. dievengatensis surprisingly were enhanced at low and intermediate concentrations of SDS (0.001 and 0.003%), while for L. marina these parameters were reduced in all SDS concentrations tested (0.001, 0.003 and 0.006%). The SDS did not affect the survivorship of adults of the slower specie. On the other hand, survivorship of adults of the fast species was significantly affected by SDS and this effect was dependent on adult gender, with reduced rates of males exposed to 0.006% SDS. Although both species are located nearby along the fast-slow continuum, they responded distinctly to of the toxic SDS effect. Effects over L. marina met the trend of faster species in allocating fewer investments in defenses against physiological injuries and on their own somatic maintenance. We propose that the apparent lower resistance of this faster species under stress at the individual level is balanced by their higher reproductive rates, conferring higher resilience to this species at the population level. Finally, it was demonstrated that the marine nematode D. dievengatensis is an important native model organism which can be used in a wide range of studies and experimental tests. Identifying and understanding differential effects of stress in the context of life-history theory is an important aspect which enhanced our understanding about the threats posed by anthropogenic activities on natural communities